Trauma magnitude of the meta-epyphyseal cancellous affects the incidence of deep vein thrombosis. A prospective cohort study on the dynamic of Collagen I, Collagen IV, Tissue factor, P-Selectin and Nitric Oxide in the thrombus formation following hip and knee surgeries. (March 2021) - Hartono, Franky; Yusuf, Irawan; Suhadi, Budhianto; Fachruddin, Andi; Augustinus, Yohanes
Abstract: Introduction: The purpose of this study was to analyze the traumatization degree of meta-epiphyseal cancellous of hip and knee joints in major orthopedic surgery that affects the incident of deep vein thrombosis (DVT) event through the dynamics expression of pro-thrombogenic biomarkers (Collagen I, Collagen IV, Tissue Factor, P-selectin) and anti-thrombogenic (Nitric Oxide). Methods: In this cohort prospective study, there were sixty-nine (69) subjects that were divided into three (3) groups, with twenty-three (23) subjects that were treated with total arthroplasty (TA), twenty-two (22) subjects were treated with hemiarthroplasty (HA), twenty-four (24) subjects were treated with open reduction internal fixation (ORIF). Subjects from May 2010 to September 2011 who met the inclusion criteria were included in this study. All patients were treated without thromboprophylaxis. Blood samples were taken in three different periods, before surgery, 72 h, and 144 h after surgery, for examination of pro-thrombogenic biomarkers (Collagen I, Collagen IV, Tissue Factor, P-selectin) and anti-thrombogenic (Nitric Oxide), which are the components involved in the hemostasis. Results: DVTs were proven by venography (or Doppler ultrasound in 8 cases) done at 144 h after the surgeries. Eighteen (18) subjects had DVT (26.1%), with ten (10) subjects from the TA group (43.5%), five (5) subjects from the HA group (22.7%), and three (3) subjects from ORIF groups (12.5) %). The risk for experiencing DVT on TA is 3.5 times more than the ORIF group, while in HA group is 2.1 times more than ORIF group. The role of biomarker levels on DVT incidence was found in Col I (p < 0.1) and NO (p < 0.05) at 72 h after surgery. Conclusion: This research confirms that trauma magnitude of the meta-epiphyseal cancellous of hip and knee joints in major orthopedic surgery influences the incidence of DVTs, through the elevation of Col I and NO. An estimated 72 h after surgery is a useful period to examine these biomarkers to help predict the diagnose of DVT. The involvement of the other biomarkers studied (Col IV, TF, and Ps) could not be proven. Future studies are needed to evaluate other biomarkers in the complex process of hemostasis to establish the diagnose of DVT. Highlights: Most major hip and knee surgery caused DVT included in three groups according to the degree of traumatization, namely one elective group for osteoarthrosis hip and knee as total arthroplasty (TA group), two non-elective groups for fracture at the femoral head as hemiarthroplasty (HA group) and fracture at femoral trochanter as internal fixation (ORIF group) Five biomarkers used to represent the dynamic component of pro- and anti-thrombogenic in the model of the hemostasis and inflammation process. Incidence of DVTs influenced by the trauma magnitude of the meta-epiphyseal cancellous bone through the elevation of Col I and NO at 72 h after surgery. The involvement of Col IV, TF and Ps have not yet been proven.